Compilation and traits of Australian bird species killed by cats. (December 2017) - Woinarski, J.C.Z.; Woolley, L.A.; Garnett, S.T.; Legge, S.M.; Murphy, B.P.; Lawes, M.J.; Comer, S.; Dickman, C.R.; Doherty, T.S.; Edwards, G.; Nankivill, A.; Palmer, R.; et al.
Abstract: House cats Felis catus have contributed to the extinction of many bird species on islands, but their impact on continental bird faunas is less well resolved. Here, we compile and analyse a comprehensive record of all bird species known to be killed by feral cats at a continental scale. From published studies and unpublished data, we document predation by feral and pet cats on 357 bird species in Australia, including 338 Australian (non-vagrant) native bird species (= 45.6% of the 741 Australian native bird species, excluding vagrants). This tally included 24 species listed as threatened or extinct by the IUCN (40% of the 58 non-vagrant Australian species listed as threatened), and 71 of the 117 bird species (61%) listed as threatened under Australian legislation (or species with one or more subspecies so listed). These tallies are substantially larger than reported in previous reviews. We provide the first continental-scale attempt to model bird species' traits that are associated with likelihood of being killed by cats, and use such modelling to attempt to redress some inevitable biases in compilation of predation records on birds. We conclude that the likelihood of being killed by a cat was highest for bird species that are restricted to islands, are of intermediate body mass ( ca. 60–300 g), and nest and forage on the ground, and least likely for bird species occurring mostly in rainforests and wetlands. We also identify a set of bird species most likely to be threatened by cat-predation and hence most likely to benefit from enhanced management of cats. This study does not specifically evaluate the impact of cats on bird populations or on the conservation of Australian birds, but our results suggest that such impact may be much more pervasive than previously documented.